Fitting Attitudes, Wrong Kinds of Reasons, and Mind-Independent Goodness - White, Heath (Journal of moral philosophy, 2009)
Abstract The 'fitting-attitudes analysis' aims to analyze evaluative concepts in terms of attitudes, but suffers from the 'wrong kind of reasons' problem. This article critiques some suggested solutions to the WKR problem and offers one of its own, which appeals to the aims of attitudes. However, goodness is not a concept that can be successfully analyzed according to the method suggested here. Reasons are given why goodness should be thought of, instead, as a mind-independent property.